Genetic Divergence and Population Structure in Weedy and Cultivated Broomcorn Millets (Panicum miliaceum L.) Revealed by Specific-Locus Amplified Fragment Sequencing (SLAF-Seq) - Li, Chunxiang; Liu, Minxuan; Sun, Fengjie; Zhao, Xinyu; He, Mingyue; Li, Tianshu; Lu, Ping; Xu, Yue (Frontiers in Plant Science, 2021)
Broomcorn millet (Panicum miliaceum L.) is one of the earliest domesticated crops in the world. Weedy broomcorn millet [Panicum ruderale (Kitag.) Chang comb. Nov. or Panicum miliaceum subsp. ruderale (Kitag) Tzvel] is thought to be the descendant of the wild ancestor or the feral type of this cereal. The phylogenetic relationships and genetic divergence among these taxa have not been clarified. In this study, the genetic diversity and population structure of weedy and cultivated broomcorn millets were investigated by using the high-throughput sequencing technology, i.e., the speciﬁc-locus ampliﬁed fragment sequencing (SLAF-seq). Results of various analyses consistently showed that both the wild and the feral types were revealed in the weedy broomcorn millets. The single nucleotide polymorphisms (SNPs) at the whole-genome level provided strong evidence to distinguish the wild and the endoferal/exoferal types of weedy broomcorn millets. The genetic divergence revealed between the cultivated broomcorn millet from eastern Eurasia and those from central-western Eurasia was probably derived from the genetic introgression from weedy broomcorn millets along the spread routes, while the limited gene flow of broomcorn millets from eastern and central-western Eurasia was probably due to the different uses of broomcorn millets and eating habits of the local people.